Does the potentially toxic cyanobacterium Microcystis exist in the soda lakes of East Africa? - Kotut, Kiplagat; Krienitz, L. (Springer, 2011)
Presently, the food chains of the famous saline alkaline flamingo-lakes of East Africa are the focus of intense scientific discussion as the lakes host toxic cyanobacteria, which when consumed by Lesser Flamingos, weaken the birds and therefore make them susceptible to attacks by infective diseases. The distribution, genetic and toxicological aspects of Microcystis in Kenya has been studied extensively. Although there are reports on the occurrence of Microcystis in Kenya’s hypersaline alkaline lakes, they have not been confirmed. Our investigations carried out over a 10-year period in about 50 inland waters showed that Microcystis occurs exclusively in freshwaters, but never in the hypersaline alkaline lakes. Microscopic examinations of the phytoplankton of these lakes revealed the presence of Anabaenopsis abijatae (Nostococales) whose lumpy structure makes it roughly similar to Microcystis when viewed under an inverted microscope. We conclude that the possible occurrence of Microcystis in hypersaline alkaline lakes is doubtful and, as such, confirmatory studies including microphotographic documentation of findings should be carried out.
DOI: 10.1007/s10750-010-0594-z
Keywords: Anabaenopsis; East Africa; Lesser Flamingo; Microcystis; Soda lakes; Toxic cyanobacteria